APPLICATION OF MEMS IN AUTOMOBILES INDUSTRY FOR INCRESAING THE SAFETY OF PASSENGERS - Phulwari, Gaurav; Khandelwal, Shani; Singodia, Dhreej (International Journal of Computer Sciences and Engineering, 2025)
The objective of this paper is towards decreasing the rate of accidents in our day to day life and increasing the safety of passengers, improving the security systems in case of vehicular theft action. Micro Electro Mechanical System (MEMS) are devices that consist of motionless or movable components with magnitude on the scale of a micrometer. One of majorly used device in MEMS is MEMS accelerometer for commercially purpose. These accelerometers typically consist of movable micro beams that determine acceleration in one or two orthogonal directions. MEMS technology contains broad variety of MEMS sensors that is widely used in the automotive industries. MEMS market is the second largest market in the world. As compared to the previous sensors MEMS sensor have advantages like fuel utilization reduction, safety advancement and is economical to vehicles. MEMS uses in automotive industry are evaluated in present and future.